Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/srep07883
|View full text |Cite
|
Sign up to set email alerts
|

Rice stripe virus affects the viability of its vector offspring by changing developmental gene expression in embryos

Abstract: Plant viruses may affect the viability and development process of their herbivore vectors. Small brown planthopper (SBPH) is main vector of Rice stripe virus (RSV), which causes serious rice stripe disease. Here, we reported the effects of RSV on SBPH offspring by crossing experiments between viruliferous and non-viruliferous strains. The life parameters of offspring from different cross combinations were compared. The hatchability of F1 progeny from viruliferous parents decreased significantly, and virulifero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 41 publications
4
26
1
Order By: Relevance
“…Furthermore, we demonstrated that RDV infection dramatically reduced the survival rates, the secreted honey, the weight, and the fecundity of N. cincticeps (Figure a‐d), consistent with previous study for S. furcifera , Recilia dorsalis , or L. striatellus infected with respective virus (Chen et al., ; Lan et al., ; Li et al., ; Nakasuji & Kiritani, ; Tu, Ling, Xu, Zhang, & Zhou, ; Wan et al., ). However, the molecular mechanism for the adverse effects on performance or fitness of N. cincticeps caused by RDV infection is still largely unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we demonstrated that RDV infection dramatically reduced the survival rates, the secreted honey, the weight, and the fecundity of N. cincticeps (Figure a‐d), consistent with previous study for S. furcifera , Recilia dorsalis , or L. striatellus infected with respective virus (Chen et al., ; Lan et al., ; Li et al., ; Nakasuji & Kiritani, ; Tu, Ling, Xu, Zhang, & Zhou, ; Wan et al., ). However, the molecular mechanism for the adverse effects on performance or fitness of N. cincticeps caused by RDV infection is still largely unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Growing evidence has shown that the persistent propagation of plant viruses adversely affects insect vectors, including prolonging the nymphal stages, shortening adult longevity, reducing survival rate, or decreasing fecundity (22,59,63,77,102,103,123). These adverse changes could be attributed to direct effects of virus-insect interactions or indirect effects of the components from diseased plants.…”
Section: Adverse Effects Of Viral Infectionmentioning
confidence: 95%
“…The small brown planthopper (Laodelphax striatellus Fallén, SBPH) (Hemiptera: Delphacidae) is an economically important pest, which causes severe damages to rice production in East Asian due to transmission of Rice stripe virus (RSV) and Rice black-streaked dwarf virus (RBSDV). 1,2 The two viruses are transmitted by SBPH in a persistent, circulative-propagative manner. 3 Somewhat differently, RSV can be transmitted from female adults to their progeny via eggs, while RBSDV has no transovarial transmission.…”
Section: Introductionmentioning
confidence: 99%